Demand for Family Planning Satisfied With Modern Methods in Urban Malawi: CHAID Analysis to Identify Predictors and Women Underserved With Family Planning Services - Alhassan, Nurudeen; Madise, Nyovani Janet (Frontiers in Global Women's Health, 2021)
Introduction: Family planning progress under the SDGs is measured with a novel indicator, demand for family planning satisfied with modern methods (mDFPS), which provides a better indication of modern contraceptive coverage than unmet need and contraceptive prevalence rate. Yet, few studies have examined the predictors of mDFPS and the sub-groups of women with unsatisfied mDFPS in urban Saharan Africa. The objective of this study was to examine the predictors of mDFPS in urban Malawi and to identify the sub-groups of urban women underserved with modern contraceptives. Methods: The study analysed data from the 2015-16 Malawi Demographic and Health survey. The sample comprised of 2,917 women in urban Malawi who had a demand for family planning services. We used a Chi-square (2) Automatic Interaction Detector (CHAID) model to address the study objectives. Results: The results show that the number of living children a woman had was the most significant predictor of mDFPS. Women with one or more children, who were of Chewa, Lomwe or Tumbuka ethnic origin, and who resided in the central region had the highest mDFPS (87%). On the other hand, women with no children, and who were not exposed to FP information on television had the lowest mDFPS (41%). Among women in union, ethnicity was the best predictor of mDFPS. Ngoni, Yao and other ethnic minority women in union who were aged 15-19 and 40 years and above, and who were Catholic, SDA/Baptist or Muslim had the lowest mDFPS (36%). Conclusion: This study demonstrates significant intra-urban disparities in demand for FP satisfied with modern contraceptives in Malawi. There is the need for policy makers and reproductive health practitioners to recognise these disparities and to prioritise the underserved groups identified in this study.